Pelapisan Calsium Carbida Permukaan Baja Karbon Rendah Dengan Pack Carburizing Energizer Serbuk Cangkang Kerang Mutiara - Sujita Darmo; Sugiman Sugiman; Salman Salman; Agus Dwi Catur; Paryanto Dwi Setyawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
The research was conducted at the Laboratory of Material Mechanics, Department of Mechanical Engineering, Mataram University. The purpose of this researchÃÂ ÃÂ  determinedÃÂ  the effect of the Pack CarburizingÃÂ  parameters (temperature, soakinÃÂ  time and carburizer media composition) on the thicknessÃÂ  of calsium carbida layerÃÂ  (CaC), which is formed on the surface of low carbon steel. The thickness of the calcium carbonate layer affects the surface hardness numberÃÂ  of low carbon steel. This research used low carbon steelÃÂ  grade SS400 as the specimen. Carburizer media is a mixture of corncob charcoal powder and Pinctada maxima shellsÃÂ  powder (PMSP).ÃÂ  Packs Carburizing was carried out at various temperatures: 875 0C, 900 0C, soakingÃÂ  time: 1,2,3 hours and the percentage of PMSP on the carburizer media: 10%, 20%, 30%. The results of the research show that the temperature carburizing , soaking time and the addition of PMSPÃÂ  affect the thickness of the calcium carbide layer on the surface of SS400 steel which is subjected to pack carburizing process. This is indicated by an increase in the surfaceÃÂ  hardness number of 421%, the wear resistance 62,2 %. ÃÂ the thickness of the calcium carbide layer 1050 ÃÂµm, the formation of pearlite structure, at the carburizing temperature of 900 0C,ÃÂ  soaking time 3 hours and 30% addition of PMSP.